The mast cell plays a central role in the immune system of teleost fish. Issue 1 (January 2015) - Sfacteria, Alessandra; Brines, Michael; Blank, Ulrich
Highlights The literature of mast cells in piscine immunology and disease is reviewed. Fish MCs possess structural and functional similarities to their mammalian counterparts. Fish models could raise an opportunity to better understand mast cell functions.